Protocol for CT in the position of discomfort: Preoperative assessment of femoroacetabular impingement – how we do it and what the surgeon wants to know. Issue 6 (4th July 2014) - Grabinski, Rafal; Ou, Daniel; Saunder, Kate; Rotstein, Andrew; Singh, Parminder; Pritchard, Michael; O'Donnell, John
Abstract Introduction The use of computed tomography of the hip in a position of discomfort (CT‐POD) in combination with 2D and 3D surface rendering is a technique increasingly used to aid in the assessment and confirmation of femoral and acetabular bony abnormalities related to femoroacetabular impingement. The purpose of this article is to describe this dynamic method of assessment. Methods Patients referred by orthopaedic surgeons for assessment of femoroacetabular impingement as part of preoperative planning and patients who required postoperative assessment of residual bony abnormalities were selected. Results This article describes the CT‐POD technique and the information required by the referring surgeon. Conclusion CT‐POD is a new technique that provides valuable preoperative and postoperative information to the surgeon.